2002
DOI: 10.1007/s00248-002-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fecal Bacterial Populations in Canines: Effects of Age, Breed and Dietary Fiber

Abstract: The effects of age, breed, and diet on fecal chemistry, enzyme activity, and bacterial populations of dogs were studied. Eighteen dogs from two age groups (young: 2.5 +/- 0.5 years, old: 10.9 +/-0.7 years) and three different breeds (German shepherds, miniature schnauzers, and English setters) were rotated through a Latin Square design such that every dog was fed each of the diets. The test diets included a low-fiber (control) diet and a 10% fiber diet which contained 5% soybean hulls and 5% beet pulp. Inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 32 publications
13
106
3
2
Order By: Relevance
“…In addition, obesity induced by ad libitum feeding was associated with a significant increase in the order Clostridiales 18. The composition of the intestinal microbiota is influenced by body fat mass, sex, diet, age, breed, and kinship 39, 40, 41. In this study, we attempted to restrict other factors that may influence gut microbiota, including breed, age, and food.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity induced by ad libitum feeding was associated with a significant increase in the order Clostridiales 18. The composition of the intestinal microbiota is influenced by body fat mass, sex, diet, age, breed, and kinship 39, 40, 41. In this study, we attempted to restrict other factors that may influence gut microbiota, including breed, age, and food.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of microbial kinds exist in animal gastrointestinal tract and feces. The intestinal microbial community which composed of 10 13 to 10 14 microorganism outnumbers the somatic and herm cells by at least an order of magnitude [2]. However, the most part of these microorganisms are uncultivable yet [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbial community which composed of 10 13 to 10 14 microorganism outnumbers the somatic and herm cells by at least an order of magnitude [2]. However, the most part of these microorganisms are uncultivable yet [2][3][4][5][6][7][8]. In the cause of coevolution of microorganisms and their hosts, the former play an important role in digestion and absorption of food, immunity, resistance to pathogens, and maintaining health of host.…”
Section: Introductionmentioning
confidence: 99%
“…So far, many scientists have been using this technique, and in literature there are many papers describing the application of DGGE in research of the structure and evolution of microbial communities from food (Ercolini, 2004), clinical samples (Li et al, 2005), soil (Campbell et al, 2009), waters (Wu et al, 2006), as well as from the rumen . DGGE has been successfully applied to the analysis of human (Chen et al, 2011), pig (Simpson et al, 1999(Simpson et al, , 2000, cattle (Kocherginskaya et al, 2001;Hernandez-Sanabria et al, 2010), dog (Simpson et al, 2002) and rodent (McCracken et al, 2001) intestinal microbial populations. Freitas et al (2008) have showed that growth of the bacterial population is increased by the presence of soyabean oil, whereas growth retardation occurred when fish oil has been used.…”
Section: Denaturing Temperature Gradient Gel Electrophoresis (Dgge/tgge)mentioning
confidence: 99%